The Changing Culture of Information Retrieval,Use and Storage in an Academic Library:A Case Study of The Faculty of The Social Sciences Library, University of Ibadan (2010)
The paper investigated the changing culture of information retrieval, its utilization and storage among students in an academic library in Ibadan, Nigeria. Data was collected through the use of questionnaire, observation and interviews. A total of two interviews with the library management of the faculty over a period of two sessions, 2007/2008 and 2008/2009, was conducted. 100 users responded to the questionanaire. The questionnaire sought to find out the frequency of library use, the value users attached to the use of the library and why they used the library. about 49% of the respondents use the library three times a week, 40% of the respondents uses the library mainly to search for ohter information apart from thier lecture notes, and 94% of the respondents showed how much value they attached to the library by thier utilization of the information sources within the library. The study also described the online information storage practices in the library; the computer literacy level of users as well as the library user-education was examined. The study found that although students used electronic sources they still preferred to consult traditional information sources such as text books and thesis. The study also revealed that 51% of students liked accessing the OPAC (Online Public Acccess Catalogue) because its is faster to use and time saving when seeking information although this is often hampered by frequent electricity cuts. On their attitude to the increased ICT presence in the library, they inistially resisted the changes but later developed interest and adapted as library use instruction as being applied. In terms of the utilization and non-utilization of the internet there were complaints from the respondents that the time allotment was too short and the computers were not enough. Other respondents mentioned the issue of the server not working at a consistent and regular basis. The study also found that libray support by top management in all its ramifications was vital in order to meet up with current trends in information service provision and development.